2020
DOI: 10.1177/1078155220951866
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of a self-cleaning automated compounding system for the decontamination of cytotoxic drugs

Abstract: Introduction Low surface contamination levels of hazardous drugs in compounding areas can be used as indicators of exposure and efficacy of cleaning procedures. We report the efficacy results of the KIRO® Oncology self-cleaning automated compounding system for decontamination of cytotoxic drugs, assessed in an oncology health center using a sanitizing method and an alkaline method. Methods The study was conducted for six-days over a three-week period. A mixture with known levels of 5-fluorouracil, ifosfamide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In most simulation studies to decontaminate antineoplastic drugs by wiping with cleaning agents, the surface is deliberately contaminated with about 100 ng to 100 µg of the drugs. 1013 The molar amounts of the drugs used for the present degradation experiments were more than those for the wiping experiments. Unless otherwise noted, a fixed volume of the ozone water (50 mL) was applied to the above amount of substance.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In most simulation studies to decontaminate antineoplastic drugs by wiping with cleaning agents, the surface is deliberately contaminated with about 100 ng to 100 µg of the drugs. 1013 The molar amounts of the drugs used for the present degradation experiments were more than those for the wiping experiments. Unless otherwise noted, a fixed volume of the ozone water (50 mL) was applied to the above amount of substance.…”
Section: Resultsmentioning
confidence: 95%
“…There have been many reports on the decontamination of antineoplastic drugs by wiping with various cleaning agents such as sodium hypochlorite, hydrogen peroxide, sodium thiosulfate, sodium hydroxide, and alcohols. [10][11][12][13] It has been demonstrated that the oxidizing agents are considerably effective for the decontamination, and sodium hypochlorite is the most potent. However, information on the degradation efficacy of the agents and the resulting products is limited.…”
Section: Introductionmentioning
confidence: 99%